Perancangan dan Implementasi Sistem Pemantauan dan Kontrol Tanaman berbasis NRF24L01 - Muhammad Agni Setyo Prawiro; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Wireless Sensor Network (WSN) is a technology concept that uses a number of nodes that have processing capabilities to achieve or complete certain tasks. In general, wireless sensor network architecture requires an embedded system or embedded sensor that is able to connect to the network and communicate through the cloud server. One of the devices commonly used in the WSN architecture is the NRF24L01 module which is a communication module based on a single frequency radio wave band. The use of a single frequency for sending and receiving data allows the transmission signal to collide with the receiving signal which causes data packets to be lost or damaged. This can be avoided by using the method of scheduling sending and receiving data. One of the scheduling methods that can be used is the Time Division Duplex (TDD) method. The concept of TDD is to give a time slot at one processing time, where the process of sending and receiving data occurs in the same frequency as each processing time. This process has a time guard that is between the time of sending data and receiving data which functions to prevent collisions between sending and receiving signals. Previous research has succeeded in implementing the TDD method on the system of sending and receiving data using Bluetooth low energy and Wi-Fi in the plant monitoring system. The test of this research is done by testing scenario of sending data based on distance variation with two parameters, namely success ratio and average delay in sending data. The distance variation used in the study is 1 meter to 10 meters. The success ratio parameter produces the lowest success ratio value of 71% at a distance of 7 meters and the highest ratio of 91% at a distance of 5 meters. Then on the average delay parameter, the delay results are 0.871 seconds on sensor node 1, 0.638 seconds on sensor node 2, and 0.644 seconds on sensor node 3.